Design and simulation of silicon optoelectronic integrated circuits - Win, Khine Thandar. (2009)
Advances in optical data storage technology have been so rapid over the past several decades for a wide range of PC and consumers electronics applications. In this new millennium, the BD (blu-ray disc) technology, the next generation to CD and DVD, using blue laser light (405nm) was introduced recently. BD technology is superior to first two generations for its higher storage capacity, usability for data storage and high-definition content delivery and backward compatibility. A main component of the blu-ray disc system, the optical pick-up unit (OPU), requires a PDIC (photodetector integrated circuit) consisting of photodetector and preamplifier.